Results of surgical repair of atrial septal defects in the middle-aged and elderly - Richmond, D. E. (1969)
Twenty-six patients aged 45 or over at the time of surgical repair of a secundum atrial septal defect have been reviewed with the object of assessing the value of the operation. Pre-operatively 12 were classed as grade IIIA or worse on the basis of their symptoms. There were six deaths in the series, three early and three late. The remaining 20 patients were improved as judged by symptoms, physical examination, and radiographic and electrocardiographic criteria. In 11 patients catheterized pre- and post-operatively, it was found that the pulmonary arterial pressure had fallen following the repair, reaching normal levels in nine. It is concluded that surgical repair of secundum atrial septal defects is of material benefit to patients of this age-group.